HIV associated pulmonary emphysema: a review of the literature and inquiry into its mechanism. Issue 5 (28th April 2008) - Petrache, I; Diab, K; Knox, K S; Twigg, H L; Stephens, R S; Flores, S; Tuder, R M
Abstract : Chronic lung diseases are increasingly recognised complications of the human immunodeficiency virus (HIV) infection and acquired immune deficiency syndrome (AIDS). Of these, pulmonary emphysema, characterised by permanent destruction of the lung parenchyma distal to the terminal bronchioles accompanied by various degrees of inflammation, is emerging as a distinct source of morbidity for patients infected with HIV. Similarly, HIV is now frequently cited as a susceptibility factor for the development of emphysema, independent of cigarette smoking status. The presence of common coexistent confounding factors that may predispose patients to chronic lung injury such as drugs, opportunistic infections and malnutrition, limits the scope of studies of direct mechanisms involved in HIV associated emphysematous lung disease. We review the clinical studies supporting a direct association between HIV infection and emphysema. Recent developments in the basic understanding of HIV infection and emphysema are also reviewed, since they may aid in understanding the pathobiology of HIV associated emphysema. The authors emphasise how HIV infection may affect cytotoxic lymphocyte activation, lung capillary endothelial cell injury and apoptosis, sphingolipid imbalance and oxidative stress in the lung. A better understanding of the pathogenesis of HIV associated pulmonary emphysema may provide clues and therapeutic targets that have broader application in this disease, including cigarette smoke induced emphysema.